Association and path coefficient analysis among yield attributes and berry yield in black pepper (Piper nigrum L.) - Shivakumar, M S; Saji, K V (Journal of Spices and Aromatic Crops, 2020)
Eighty two germplasm accessions of black pepper aggregated from pepper cultivating tracts of Karnataka, Kerala, Goa and Maharashtra were characterized for 17 quantitative traits as per the IPGRI descriptors during 2018-19 at the field gene bank of ICAR-Indian Institute of Spices Research, Experimental Farm, Kozhikode. Wide range and high coefficient of variation (CV) were recorded for dry berry weight, fresh berry weight and number of spikes vine-1 whereas, lower CV was observed for berry size. Fresh berry weight showed significant positive correlation with dry berry weight followed by number of spikes vine-1 whereas, number of immature berries spike-1 and berry size showed significant negative association with setting percentage. High positive direct effect of fresh berry weight on dry berry weight was observed during path analysis. Both fresh rachis weight and number of spike vine-1 had indirect positive effects on dry berry weight through fresh berry weight. Residual effect was meagre suggesting that the 17 quantitative traits explained 99% variability. Traits like number of spikes vine-1 and fresh berry weight are the important traits that need to be augmented during improvement of black pepper for yield.